Ecologia de bandos mistos de aves na Estação Ecológica de Itirapina, Estado de São Paulo - Reis, Matheus Gonçalves dos (2011)
The degradation of natural grassland and open area remnants is still intense and affect environmental integrity of these ecosystems. The mixed-flocks of birds are a common feature in open environments which provide advantages to members. We aimed to analyze mixed-flocks of birds in three open physiognomies of cerrado to verify differences among sampled areas and periods. We believe that mixed-flock structure changes according to the physiognomy and between the seasons. We followed and record 337 mixed-flocks formed by 45 bird species between July 2008 and December 2010, in Estação Ecológica de Itirapina, São Paulo state. The flocks of campo limpo (grassland vegetation) had a lower participation of species than flocks from other areas, and structure did not varied significantly between breeding (summer) and non-breeding (winter) period. Two species formed flocks only in campo limpo . The campo sujo (grassland with scattered shrubs), considered an intermediate environment in our study, had no exclusive species. The seasonal variation in flock structure was significant. The campo cerrado (shrubby-grassland with many scattered trees) indicates the same differentiation between seasons. We found similarities between the breeding period of campo sujo and campo cerrado . Twelve species were present only in flocks of campo cerrado with low occurrence frequencies; all of them are birds of more wooded or forested environments. We categorized species according to their function played in mixed-flocks: True Leaders, Leaders/Followers, True Followers, Occasional Followers, Migrants. Five species played a role as True Leaders, and nine species can be considered as nuclear species of mixed-flocks. Saltator atricollis, Neothraupis fasciata and Cypsnagra hirundinacea were the most 29 common True Leaders. The formation of mixed-flocks, a phenomenon which benefits its members, were recorded in open areas of savanna throughout the year, but were especially important for birds during the period of resources scarcity. Nine flocking species, 20% of all species observed in this study, are threatened in São Paulo state and have high ecological relevance.